2009
DOI: 10.3390/molecules14082862
|View full text |Cite|
|
Sign up to set email alerts
|

A New Sesquiterpene from the Fruits of Daucus carota L.

Abstract: Phytochemical investigation of the fruits of Daucus carota L. resulted in the isolation of a new sesquiterpene named as daucucarotol (1). Its structure was elucidated on the basis of 1D and 2D NMR experiments, coupled with MS studies. To our knowledge, compound 1 is the first example for a natural eudesmane sesquiterpene with a hydroxymethyl group located at a methine carbon rather than a usual quaternary carbon in the two fused six-membered ring systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The chemical composition of the Daucus carota oil, extracted from different parts of the plant, consists mainly of phenylpropanoids, monoterpenes, sesquiterpenes and phenols in addition to polyphenols which include flavonoids (Gonny et al, 2004;Staniszewska et al, 2005;Rossi et al, 2007;Maxia et al, 2009;Wei Fu et al, 2009, 2010. A study on the dichloromethane-methanol extract of the flower of wild carrot from Turkey, using the 1,1-diphenyl-2-picryl hydrazyl (DPPH) method, revealed significant antioxidant activity (Akgul et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of the Daucus carota oil, extracted from different parts of the plant, consists mainly of phenylpropanoids, monoterpenes, sesquiterpenes and phenols in addition to polyphenols which include flavonoids (Gonny et al, 2004;Staniszewska et al, 2005;Rossi et al, 2007;Maxia et al, 2009;Wei Fu et al, 2009, 2010. A study on the dichloromethane-methanol extract of the flower of wild carrot from Turkey, using the 1,1-diphenyl-2-picryl hydrazyl (DPPH) method, revealed significant antioxidant activity (Akgul et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigation of the fruits of Daucus carota resulted in the isolation of a new sesquiterpene named as daucucarotol. It was the first example for a natural eudesmane sesquiterpene with a hydroxymethyl group located at a methine carbon rater than a usual quaternary carbon in the two fused six-membered ring systems [87]. Daucane-type sesquiterpenes such as as trans-dauc-8-ene-4b-ol, trans-dauca-8,11-diene, dauca-5,8-diene, acora-4,9-diene, acora-4,10-diene, carotol, daucol and daucucarotol were isolated from Daucus carota [78,[87][88][89].…”
mentioning
confidence: 99%
“…It was the first example for a natural eudesmane sesquiterpene with a hydroxymethyl group located at a methine carbon rater than a usual quaternary carbon in the two fused six-membered ring systems [87]. Daucane-type sesquiterpenes such as as trans-dauc-8-ene-4b-ol, trans-dauca-8,11-diene, dauca-5,8-diene, acora-4,9-diene, acora-4,10-diene, carotol, daucol and daucucarotol were isolated from Daucus carota [78,[87][88][89]. Ahmed et al, isolated four sesquiterpenes daucane esters, one polyacetylene, one sesquiterpene coumarin, and sitosterol glucoside from the roots of the wild Daucus carota ssp carota [90].Extracts of fresh roots and foliage of the garden carrot (Daucus carota) were analyzed for linear furocoumarins (psoralens) compared with standard psoralen, xanthotoxin, bergapten, isopimpinellin, heraclenin, and oxypeucedanin.…”
mentioning
confidence: 99%
“…These spectral features were closely related to those of daucucarotol [15], except for a tertiary methyl signal in 2 instead of an oxygenated methylene signal in daucucarotol. The HMBC spectrum of 2 displayed cross-peaks from the doublet methyl signal at  H 0.85 to C-1, C-2, and C-10, which suggested that the doublet methyl group located at C-1.…”
Section: Extraction and Isolationmentioning
confidence: 63%